Multimodal lipid-lowering treatment in pediatric patients with homozygous familial hypercholesterolemia: target attainment requires further increase of intensity - Klaus, Günter; Schmitt, Claus P. (Pediatric nephrology, 2018)
Familial hypercholesterolemia (FH) causes premature cardiovascular disease (CVD). Lipoprotein apheresis (LA) is recommended as first-line lipid-lowering treatment (LLT) for homozygous (ho) FH.
Gesehen am 28.10.2019